INFLUENCE OF THE USE OF WHATSAPP SOCIAL MEDIA ON THE RESULTS OF LEARNING GERMAN OF STUDENTS OF SMA NEGERI 20 MALUKU TENGAH - Cecilia Meideline Pattiselanno; Juliaans E R Marantika; G H Kunu (JURNAL TAHURI, 2022)
This research aims to explain the influence of whatsApp's use of social media as a learning medium on german learning outcomes. This study has two variables, namely the use of WhatsApp social media as a learning medium (X) as a free variable and german learning outcomes as bound variables (Y). The method used in this study is Ex Post Facto. This research data is obtained through interviews, questionnaires and results of learning German odd semesters (Midterms and End Semester Exams) through documentation studies. WhatsApp social media as a learning medium is used through interviews with teachers and questionnaires given to German learners. The data of the questionnaire results is processed with a likert scale then analyzed using percentage descriptive analysis techniques, then the results of German learning are processed with the T-Test technique. The results of the German language learning process showed that the use of Whatsapp social media as a learning medium had a positive effect on german learning outcomes